Unsex CEDAW, or What’s Wrong with Women’s Rights - Rosenblum, Darren (Columbia Journal of Gender and Law, 2011)
Before I go on, I want to tell a story. During high school, I had an English teacher who often wore a pendant from the National Organization of Women. I asked her about it and we began a conversation that continued for years as she fed my voracious mind with Gloria Steinem, Alice Walker and other feminist literature. One day, on my way home from a meeting of Gay and Lesbian Youth of New York, I picked up the Village Voice and saw an announcement for a women’s rights conference. My dad drove me into the city for the conference, which well over a thousand people attended. As part of the forum, individuals reported back from the 1985 World Conference on Women held in Nairobi. As people entered the hall, a slide show of conference photos ran alongside Helen Reddy’s “I am Woman.” Perhaps two or three men were there. Throughout the day, attendees approached me to inquire where they could find coffee or if I was in the right place. As a sixteen- year old boy with darker-than-average skin, I must have struck the attendees as some sort of coffee bo’. Why else would I be there?